British and Irish Association of Law Librarians (BIALL) Legal Information Literacy Statement - Choolhun, N; Bird, R (Chartered Institute of Librarians and Information Professionals, 2012)
The Association hosts an annual conference which features a members’ ‘Have your say’ session. At the 2011 session, a BIALL member based in the commercial sector voiced their concern at the legal research competency of recent joiners to their firm, stating that senior partners were asking in-house law librarians to verify the research presented by new trainees. This member also queried the role of academic law librarians, questioning how legal research skills are being taught at academic and vocational level and stating clearly that the legal research skills of new joiners are not meeting the expectations of employers. The following debate prompted one of the authors to propose that BIALL should investigate the issue in depth, with the aim of producing legal IL guidance in the form of a toolkit, similar to legal IL guidance devised in the United States and IL initiatives within the NHS (Choolhun 2012).